High-resolution spectroscopic study of the H2O–CO2 van der Waals complex in the 2OH overtone range. (2nd June 2020) - Lauzin, C.; Imbreckx, A. C.; Foldes, T.; Vanfleteren, T.; Moazzen-Ahmadi, N.; Herman, M.
Abstract : The jet-cooled spectrum ( T r o t = 12 K) of the H 2 O–CO 2 van der Waals complex has been recorded in the 1.4 μm region by cavity ring-down spectroscopy. Two b -type vibrational bands have been observed and analysed. The rotational assignment has been achieved using a different asymmetric rotor Hamiltonian for each nuclear spin species, accounting for the internal rotation of the H 2 O and CO 2 units. The band at 7247 cm − 1 is assigned to (101) in terms of the ( v 1 v 2 v 3 ) vibrational quantum number of the H 2 O monomer. The band at 7238 cm − 1 is assigned to (200) + an intermolecular mode ( v 12 ) excited in the complex. Vibration-rotation constants are provided for the excited states. The symmetry of the wavefunction, the effect of vibrational excitation on the tunnelling dynamics and the vibrational assignment are discussed. GRAPHICAL ABSTRACT: